Occupational therapy evaluation for adults : a pocket guide - Vroman, Kerryellen; Stewart, Elizabeth (Elizabeth Anne); Neistadt, Maureen E. (Philadelphia : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
'Dr. Maureen Neistadt created the first edition of Occupational Therapy Evaluation for Adults: A Pocket Guide as a readily accessible tool for occupational therapy practitioners, most especially fieldwork students, those in their first year of practice, and more seasoned practitioners new to working with adults. I remember her bounding into my office with the first draft of the table of contents and how she, with her characteristic logic and enthusiasm, explained the purpose of the book. Maureen had an extraordinary capacity to understand her audience whether she was teaching or writing a scholarly article or text book'--Provided by publisher.
Evaluation process in occupational therapy -- The occupational therapy practice framework and relationship to the evaluation process -- The occupational therapy practitioner's clinical thinking -- The evaluation process : referral and interview -- Evaluation of occupational patterns and performance -- Assessing motor performance -- Evaluation of cognitive performance skills and assessment tools -- Evaluation of visual/perceptual performance skills and assessment tools -- Evaluation and assessment tools for the environment -- Considerations in goal writing.
Preceded by: Occupational therapy evaluation for adults / Maureen E. Neistadt. 2000.
Includes bibliographical references and index.
Keywords: Occupational Therapy -- handbooks; Occupational therapy -- Handbooks, manuals, etc